2000
DOI: 10.1093/jn/130.3.507
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid Suppresses the Increase in Disaccharidase Activity That Occurs during Culture of Caco-2 Cells

Abstract: To understand how blood glucose level is lowered by oral administration of vinegar, we examined effects of acetic acid on glucose transport and disaccharidase activity in Caco-2 cells. Cells were cultured for 15 d in a medium containing 5 mmol/L of acetic acid. This chronic treatment did not affect cell growth or viability, and furthermore, apoptotic cell death was not observed. Glucose transport, evaluated with a nonmetabolizable substrate, 3-O-methyl glucose, also was not affected. However, the increase of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 33 publications
1
60
1
5
Order By: Relevance
“…Another approach for investigating the effect of vinegar is to analyze the enzymes involved in glucose digestion or glucose metabolism. Ogawa et al (2000) examined the effects of acetic acid and other organic acids on disaccharidase activity in CACO-2 human colon cancer cells. Disaccharidases are glycoside hydrolases, which are enzymes that break down disaccharides into monosaccharides, including sucrose, lactase, and maltase.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach for investigating the effect of vinegar is to analyze the enzymes involved in glucose digestion or glucose metabolism. Ogawa et al (2000) examined the effects of acetic acid and other organic acids on disaccharidase activity in CACO-2 human colon cancer cells. Disaccharidases are glycoside hydrolases, which are enzymes that break down disaccharides into monosaccharides, including sucrose, lactase, and maltase.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, Fushimi et al (2001) showed that acetic acid could activate gluconeogensis and induce glycogenesis in the liver after a fasting state. Furthermore, when Caco-2 cells (human colonic carcinoma cells) were cultivated with acetic acid for 15 days, Ogawa et al (2000) showed that acetic acid suppresses the increase in disaccharidase activity (sucrase, maltase, trehalase and lactase). These two latter studies add pieces of evidence to the knowledge on how acetic acid affects glucose absorption and metabolism, but more research is needed to understand the importance of each physiological phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed to evaluate the potential effects of acetic acid on glucose metabolism. Acetic acid has thus been shown to suppress disaccharidase activity in Caco-2 cells (human colonic carcinoma cells) (Ogawa et al, 2000) and to activate gluconeogenesis and induce glycogenesis in the rat liver after a fasting state (Fushimi et al, 2001). Although it has been established that the presence of acetic acid in a meal delays the gastric emptying rate and thus reduce postprandial glycaemia (Ebihara & Nakajima, 1988;Liljeberg & Björck, 1998), more studies are needed to elucidate to what extent other physiological mechanisms also may be involved and affect glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%